IS THE STUDENT ADAPTATION TO COLLEGE QUESTIONNAIRE APPROPRIATE TO MEASURE STUDENTS’ COLLEGE ADJUSTMENT? - Rifameutia, Tjut; Malay, Elok D. (Jurnal Psikologi, 2023)
College adjustment (CA), or adaptation to college life, has been proven to predict college student achievement and persistence during their college study. Therefore, measuring students’ college adjustment from the first year of study would be fundamental. Indonesia needs a valid and reliable instrument to measure college adjustment accurately. This study investigates the validity and reliability of SACQ (Student Adaptation to College Questionnaire), an adapted version to Bahasa Indonesia. SACQ is a widely used measurement tool for college adjustment developed by Baker and Siryk (1984). This study uses a Confirmatory Factor Analysis to measure the validity and reliability of SACQ as a GPA predictor. The result shows that the Indonesian adaptation version of SACQ is valid and reliable in measuring college students’ adjustment, χ 2 (1, N = 1033) = 1.01, p = .315; RMSEA = .003. The impact of this study is that Indonesia can widely use this instrument to measure the level of college adjustment.